Formation of good Christian conscience: A link between professed faith and praxis in Africa - Moyo, Masauso (Acta theologica, 2025)
The congruency of professed Christian faith with its corresponding conscience is critical for the church to embody the servanthood of Christ that would rid Africans of poverty and hegemonic vices (Verster 2022:59). However, according to Boesak (2005:39), Africa has enfeebled public conscience. Meanwhile the church is accused of practising the "wrong type of Christianity" typified by dualistic, escapist, pietistic, and ecclesiastic tendencies (Van der Watt 2003:53-54). In addition, the church is allegedly practising false neutrality, theology of disinterest, and passivity on matters affecting respective African communities (Botha & Makofane 2019:90; Fiorenza 1988:4). Using data collected from literature review, this article hermeneutically explores the possibilities of forming a theocentric conscience for actualising the church’s embodiment of a servanthood that would aid social transformation in African contexts. It proposes a formation that facilitates shifts from disinterest to interest; false neutrality to active participation; complacency to principled conscience, as well as dependence and begging syndrome to self-reliance.